Performance Analysis of Regional Civil Service Agency of The Rembang District - Natalia Kusuma Dewi; Hardi Warsono; Ida Hayu Dwimawanti (Program Pascasarjana Universitas Negeri Makassar, 2020)
Performance measurement of a public organization has been an issue in recent years. The State Apparatus has become a pioneer in the success of development to achieve justice and welfare of society. . Negative issues regarding professionalism, especially in the quality and performance aspects of ASN, need to be responded positively by conducting an evaluation. The public generally views that the problem of ASN professionalism can be seen from the lack of integrity, low competence, slow performance, and many disciplinary violations. The Rembang Regency Regional Personnel Agency has carried out a performance appraisal with reference to the Rembang Regency Regional Personnel Agency Performance Agreement in 2019. The assessment provides an overview of the successes and failures in achieving the resulting goals and targets, then categorizing performance (positioning) according to the level of performance achievement. The results of the performance achievement show that the average performance achievement of the Rembang Regency Regional Personnel Agency in 2019 is 90.98%. Coordinate with the Central Government regarding the activities to be implemented so that they can meet the targets for implementing these activities.